A proposed Common Training Framework for Specialists in Laboratory Medicine under EU Directive 2013/55/EC (The Recognition of Professional Qualifications) - Wieringa, G.; Queralto, J.; Homsak,E.; Jassam,N.; Cavalier,E.; Svinarov,D.; Krleza,J.L.; Christou,S.; Pikner,R.; Larsen,T.R.; Tomberg, K.; Linko-Parvinen,A.; et al. (Clin.Chem.Lab Med., 2021)
European Union (EU) Directive 2013/55/EC (The Recognition of Professional Qualifications) allows Member States to decide on a common set of minimum knowledge, skills and competences that are needed to pursue a given profession through a Common Training Framework. To be adopted the framework must combine the knowledge, skills and competences of at least one third of the Member States. Professionals who have gained their qualifications under a Common Training Framework will be able to have these recognised automatically within the Union. The backbone of the European Federation of Clinical Chemistry and Laboratory Medicine's (EFLM) proposed Common Training Framework for non-medical Specialists in Laboratory Medicine is outlined here. It is based on an Equivalence of Standards in education, training, qualifications, knowledge, skills, competences and the professional conduct associated with specialist practice. In proposing the recognition of specialist practice EFLM has identified 15 EU Member States able to meet Equivalence and in whom the profession and/or its training is regulated (an additional EU Commission requirement). The framework supports and contributes to the Directive's enabling goals for increasing professional mobility, safeguarding consumers and ensuring a more equitable distribution of skills and expertise across the Member States. It represents EFLM's position statement and provides a template for professional societies and/or competent authorities to engage with the EU Commission
Keywords: Chemistry,Clinical; Curriculum; European Union; Greece; Humans; Laboratories; Specialization